Lepanthes gibbosa (Orchidaceae: Pleurothallidinae), a new species from Costa Rica - Bogarín, Diego; Lara-Guerrero, Sofia; Camacho-Solis, Yesly (Phytotaxa, 2025)
Lepanthes is one of the most diverse genera in the Neotropics, representing a significant portion of Costa Rica’s orchid flora. However, the taxonomic identification and delimitation of Lepanthes species remain incomplete, particularly in the highly diverse regions of the Neotropics. While previous studies have recorded Lepanthes demissa in Costa Rica, some of these records actually correspond to an undescribed species that morphologically resembles Lepanthes mentosa. This study aims to clarify the taxonomic status of populations previously identified as L. demissa in Costa Rica. Our findings indicate that L. demissa is restricted to southern Costa Rica and western Panama along the Cordillera de Talamanca. In contrast, the populations from central Costa Rica previously assigned to this species represent a distinct, undescribed species, which we name here as L. gibbosa. The new species resembles L. mentosa but can be distinguished by its longer ramicauls, longer coflorescences, yellowish-white flowers with red veins, orange petals marked with a red spot, upper petal lobes that are convergent and longer than the lower lobes, the lip with oblong-ovate lobes, 1.0–1.3 mm long with an oblong, external, subquadrate, slightly reflexed appendix and a column that is concealed by the thick body when viewed from the front. Additionally, we provide detailed information on its distribution, habitat, phenology, and conservation status. Conservation efforts should prioritize ongoing fieldwork to confirm the presence of L. gibbosa within protected areas.